Genetics of congenital heart disease. (May 2016) - Edwards, Jonathan J.; Gelb, Bruce D.
Abstract : Purpose of review: The goal of this review is to highlight recent discoveries in the field of genetics as it relates to congenital heart disease (CHD). Recent advancements in next generation sequencing technology and tools to interpret this growing body of data have allowed us to refine our understanding of the molecular mechanisms that result in CHD. Recent findings: From multiple different study designs, the genetic lesions that cause CHD are increasingly being elucidated. Of the more novel findings, a forward genetic screen in mice has implicated recessive inheritance and the ciliome broadly in CHD pathogenesis. The developmental delays frequently observed in patients with CHD appear to result from mutations affecting genes that overlap heart and brain developmental regulation. A meta-analysis has provided clarity, discriminating pathologic from incidental copy number variations and defining a critical region or gene. Summary: Recent technological advances have rapidly expanded our understanding of CHD genetics, and support the applicability to the clinical domain in both sporadic and inherited disease. Though significant gaps remain, genetic lesions remain the primary explanation for CHD pathogenesis, although the precise mechanism is likely multifactorial.